Migration mechanism of grouting slurry and permeability reduction in mining fractured rock mass - Cao Zhengzheng; Wang Pengshuai; Li Zhenhua; Du Feng (Scientific Reports, 2024)
Abstract In order to solve the water and gas discharge hazard caused by gob water and harmful gases (such as CO), the method of grouting overburden fractures is adopted to achieve the purpose of safe and efficient mining production in coal mines. This paper carries out the experimental research on the permeability reduction effect of grouting in fractured rock mass, expounds the relationship between gas flow rate and pressure gradient, seepage pressure and permeability, confining pressure and permeability, and analyzes the permeability change law of fractured rock mass before and after grouting. Besides, the grouting migration and permeability reduction model of fractured fine-grained sandstone is constructed by combining grouting test and numerical simulation, which reveals the dynamic evolution law of rock mass permeability in the grouting process. The results show that the permeability of the grouting rock sample decreases from 700–13,000 to 15–300 mD than that of the ungrouting rock sample, and the decrease is more than 95%, which indicates that the sealing performance of grouting slurry is better. Besides, numerical simulations show that the initial permeability of rock samples is 971.9 mD, and the permeability decreases to 45.79 mD after 1800s, and the permeability decreases to 95.3%, which is basically consistent with the experimental results after grouting. The greater the grouting pressure is, the better the grouting effect is. With the increase of the grouting pressure, the increase of the grouting effect is no longer obvious.